Caring for the carers: Advice for dealing with sleep problems of hospital staff during the COVID‐19 outbreak. (8th June 2020) - Ballesio, Andrea; Lombardo, Caterina; Lucidi, Fabio; Violani, Cristiano
Abstract: Hospital staff are at the frontline in the COVID‐19 outbreak. The stressors they experience may induce sleep problems in a population already at risk. Sleep deprivation, long shifts and insomnia in hospital staff have been associated with individual, organizational and public health hazards. These include increased risk of mental and somatic disorders, altered immune responses, medical errors, misunderstandings, drowsy driving and burnout. In March 2020, the World Health Organization called for providing access to mental health and counselling for health professionals involved in the COVID‐19 outbreak. To answer this call, we propose practical advice for the management of sleep problems (sleep deprivation, insomnia and shift work) that can be included in supportive interventions. The advice is based on psychobiological principles of sleep regulation and on guidelines for the treatment of insomnia and was implemented within an initiative offering psychological support to the staff of three university hospitals in Rome.